2018
DOI: 10.1177/0269215518808000
|View full text |Cite
|
Sign up to set email alerts
|

What factors affect clinical decision-making about access to stroke rehabilitation? A systematic review

Abstract: Objectives:To determine the factors affecting clinical decision-making about which patients should receive stroke rehabilitation.Methods:Data sources (MEDLINE, CINAHL, AMED and PsycINFO) were searched systematically from database inception to August 2018. Full-text English-language studies of data from stroke clinicians were included. Studies of patients were excluded. The included studies were any design focussed on clinical decision-making for referral or admission into stroke rehabilitation. Summary factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 26 publications
4
41
1
2
Order By: Relevance
“…In a survey investigating 187 occupational therapists' clinical decision-making regarding management of sensory impairments post-stroke in the United States, clinical knowledge was found to influence occupational therapists' decisions to conduct assessments of post-stroke upper limb sensory impairment, while clinical knowledge, experience, and contextual factors influenced decisions about intervention (Doyle, Bennett, & Gustafsson, 2013). When considering access to post-stroke rehabilitation, a recent systematic review found that patient-related factors, organisational factors, and the characteristics of individual clinicians all influenced decision-making (Longley et al, 2019). These factors, and the studies from which they are drawn, will be discussed in the following sections.…”
Section: Clinical Decision-makingmentioning
confidence: 99%
See 4 more Smart Citations
“…In a survey investigating 187 occupational therapists' clinical decision-making regarding management of sensory impairments post-stroke in the United States, clinical knowledge was found to influence occupational therapists' decisions to conduct assessments of post-stroke upper limb sensory impairment, while clinical knowledge, experience, and contextual factors influenced decisions about intervention (Doyle, Bennett, & Gustafsson, 2013). When considering access to post-stroke rehabilitation, a recent systematic review found that patient-related factors, organisational factors, and the characteristics of individual clinicians all influenced decision-making (Longley et al, 2019). These factors, and the studies from which they are drawn, will be discussed in the following sections.…”
Section: Clinical Decision-makingmentioning
confidence: 99%
“…This highlights the complexity of the decisions made by clinicians. As echoed in the recent systematic review by Longley et al (2019), research has been conducted to examine the patient, therapist and organisational factors that contribute to clinicians' decision-making around rehabilitation after stroke, but how these factors are integrated on the acute wards, and by rehabilitation assessors, has not been fully investigated within the stroke care context. Furthermore, given the variations between sites observed in audit data, and the importance of organisational factors in rehabilitation service referral and receipt, described in the sections above, it is expected that decision-making processes will vary between sites.…”
Section: Gaps In Knowledge Of Rehabilitation Referral Practicesmentioning
confidence: 99%
See 3 more Smart Citations